EFFECTS OF COVER BOARD AGE, SEASON, AND HABITAT ON THE OBSERVED ABUNDANCE OF EASTERN RED-BACKED SALAMANDERS (PLETHODON CINEREUS) - Smith, Geoffrey R.; Grasser, Cody N (Journal of North American Herpetology, 2014)
Plethodontid salamanders are potentially good ecological indicator species in woodland habitats due to their abundance and sensitivity to changes in the environment. The use of terrestrial salamanders as ecological indicators depends on effective means of surveying their abundance and distribution. Our study examined the use of old and new artificial cover boards by Eastern Red-backed Salamanders (Plethodon cinereus). We also considered the effects of season (spring vs. fall) and habitat type (deciduous vs. coniferous vs. mixed) on cover board use by P. cinereus. Our results indicated that P. cinereus abundance was greater under old cover boards compared to new cover boards. However, the difference between the use of old and new cover boards was greater during the spring than the fall, suggesting that the effect of cover board age became weaker over time. Plethodon cinereus showed strong seasonal variation in observed abundance, with peaks during the spring and fall seasons and very low surface activity during the summer. Plethodon cinereus had higher observed abundance in deciduous habitats than in coniferous and mixed habitats. Our results suggested that care should be taken to account for cover board age in long-term monitoring programs, especially if cover boards are replaced during a study.